2004
DOI: 10.1074/jbc.m401390200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inducible Nitric-oxide Synthase by Activators of AMP-activated Protein Kinase

Abstract: AMP-activated protein kinase (AMPK), an energysensing enzyme that is activated in response to cellular stress, is a critical signaling molecule for the regulation of multiple metabolic processes. AMPK has recently emerged as an attractive novel target for the treatment of obesity and type 2 diabetes because its activation increases fatty acid oxidation and improves glucose homeostasis. Here we show that pharmacological activation of AMPK by insulin-sensitizing drugs markedly inhibits inducible nitric-oxide syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
122
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 58 publications
9
122
0
Order By: Relevance
“…Our assessment of mRNA levels of MCP-1 revealed that expression of MCP-1 is decreased in Wnt10b-A y mice. While only a trend toward reduced expression of F4/80 was also noted (not shown), iNOS expression, one possible mediator of inflammation-associated insulin resistance (43,45), is reduced by 73% in white adipose tissue of Wnt10b-A y mice (Fig. 3E).…”
Section: Resultsmentioning
confidence: 96%
“…Our assessment of mRNA levels of MCP-1 revealed that expression of MCP-1 is decreased in Wnt10b-A y mice. While only a trend toward reduced expression of F4/80 was also noted (not shown), iNOS expression, one possible mediator of inflammation-associated insulin resistance (43,45), is reduced by 73% in white adipose tissue of Wnt10b-A y mice (Fig. 3E).…”
Section: Resultsmentioning
confidence: 96%
“…AMPK can also inhibit cholesterol and fatty acid biosynthesis via phosphorylation and inhibition of acetyl CoA-carboxylase and HMG CoA-reductase (9,11). Previously, it was reported by us and others that AICAR inhibits the production of proinflammatory mediators TNF-␣, IL-1␤, IL-6, and NO in primary astrocytes, microglia, and M (23,37,38). Therefore, the observed antiinflammatory effects of AICAR on EAE are likely mediated through both immune-independent and -dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al (41) demonstrated that the treatment of obese mice with salicylate results in a significant decrease in blood glucose levels, whereas clinical trials with salsalate, a non-acetylated prodrug of salicylate, showed a reduction in blood glucose levels in patients with T2D (42). In obesity and T2D, the accumulation of saturated fatty acids such as palmitate results in deactivation of AMPK, and this decreases autophagy and NO production and increases mitochondrial dysfunction and mitochondrial ROS production (43). This leads, in turn, to activation of the NLRP3 inflammasome.…”
Section: Role Of Nad ؉ Sirtuins and Amp-dependent Protein Kinase Imentioning
confidence: 99%